Hot and Hypoxic Environments Inhibit Simulated Soccer Performance and Exacerbate Performance Decrements When Combined - Aldous, Jeffrey W. F.; Chrismas, Bryna C. R.; Akubat, Ibrahim; Dascombe, Ben; Abt, Grant; Taylor, Lee (Frontiers in Physiology, 2016)
The effects of heat and/or hypoxia have been well-documented in match-play data. However, large match-to-match variation for key physical performance measures makes environmental inferences difficult to ascertain from soccer match-play. Therefore, the present study aims to investigate the hot (HOT), hypoxic (HYP) and hot-hypoxic (HH) mediated-decrements during a non-motorised treadmill based soccer-specific simulation. Twelve male University soccer players completed three familiarisation sessions and four randomised crossover experimental trials of the intermittent Soccer Performance Test (iSPT) in normoxic-temperate (CON: 18oC 50% rH), HOT (30oC; 50% rH), HYP (1,000m; 18oC 50% rH) and HH (1,000m; 30oC; 50% rH). Physical performance and its performance decrements, body temperatures (rectal, skin and estimated muscle temperature), heart rate (HR), arterial blood oxygen saturation (SaO2), perceived exertion, thermal sensation (TS), body mass changes, blood lactate and plasma volume were all measured. Performance decrements were similar in HOT and HYP [Total Distance (-4%), High-speed distance ( -8%) and variable run distance ( -12%) covered] and exacerbated in HH [total distance (-9%), high-speed distance (-15%) and variable run distance (-15%)] compared to CON. Peak sprint speed, was 4% greater in HOT compared with CON and HYP and 7% greater in HH. Sprint distance covered was unchanged (p > 0.05) in HOT and HYP and only decreased in HH (-8%) compared with CON. Body mass (-2%), temperatures (+ 5%) and TS (+18%) were altered in HOT. Furthermore, SaO2 (-7%) and HR (+3%) were changed in HYP. Similar changes in body mass and temperatures, HR, TS and SaO2 were evident in HH to HOT and HYP, however, blood lactate (p < 0.001) and plasma volume (p < 0.001) were only significantly altered in HH. Perceived exertion was elevated (p < 0.05) by 7% in all conditions compared with CON. Regression analysis identified that absolute TS and absolute rise in skin and estimated muscle temperature (r = 0.82, r = 0.84 r = 0.82, respectively; p <0.05) predicted the hot-mediated-decrements in HOT. The hot, hypoxic and hot-hypoxic environments impaired physical performance during iSPT. Future interventions should address the increases in TS and body temperatures, to attenuate these decrements on soccer performance.